Crustal architecture of the Indian Ocean Sector of the Antarctic continent: summary of the current phase IX and towards the next phase X (JARE 65-) - Hokada, Tomokazu; JARE, geology group undefined (2022)
The 13th Symposium on Polar Science/Special session [S] Towards the next six-year Japanese Antarctic Research Project (phase X), Tue. 15 Nov. conference object